2015
DOI: 10.1016/j.cgh.2014.11.036
|View full text |Cite
|
Sign up to set email alerts
|

Identification and Characterization of Cefazolin-Induced Liver Injury

Abstract: Background &Aims Cephalosporin antibiotics are popular because they have a broad spectrum of activity and are generally well tolerated; cephalosporin-induced liver injury is considered to be rare. We describe a new syndrome associated with a single intravenous dose of cefazolin and the clinical features of cephalosporin-induced liver injury. Methods The drug-induced liver injury (DILI) network collected detailed clinical data on 1212 patients with DILI between 2004 and 2012. We analyzed data from 41 patients… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
47
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 50 publications
(49 citation statements)
references
References 30 publications
1
47
0
1
Order By: Relevance
“…Here, we have demonstrated that AC is the most common cause of idiosyncratic liver injury in the DILIN data set and that, like other penicillins and cephalosporins, it causes predominantly a cholestatic-type liver injury [5, 14]. In addition, DILI due to AC, unlike DILI due to other drugs, appears to preferentially afflict older men.…”
Section: Discussionmentioning
confidence: 99%
“…Here, we have demonstrated that AC is the most common cause of idiosyncratic liver injury in the DILIN data set and that, like other penicillins and cephalosporins, it causes predominantly a cholestatic-type liver injury [5, 14]. In addition, DILI due to AC, unlike DILI due to other drugs, appears to preferentially afflict older men.…”
Section: Discussionmentioning
confidence: 99%
“…However, drug‐induced liver injury from cephalosporins is uncommon and characteristically manifests as a cholestatic pattern of abnormal liver biochemistry that occurs at least one week after the drug, not during the first few days post‐operatively . It should be noted that ceftriaxone differs from other cephalosporins, and has been associated with biliary sludge, cholecystitis and cholestatic jaundice …”
Section: Discussionmentioning
confidence: 99%
“…Amoxicillin-clavulanate, typically given as a 10-day course, is associated with a cholestatic hepatitis that may not been seen for one to three weeks after the drug is stopped 16 . A single dose of cefazolin, given as antibacterial prophylaxis prior to surgery, is associated with cholestatic injury that manifests up to three weeks later 68 . Toxicological analysis may be helpful in the follow-up evaluation of DILI, but with the exception of tests for acetaminophen adducts, may not be available in real time.…”
Section: Final Analysis and Consultative Opinionmentioning
confidence: 99%